The working lives of women and their retirement - Austen, Siobhan; Birch, Elisa (Curtin University of Technology, 2001)
Within the current retirement system in Australia, arrangements are predominantly based on the age-pension and private superannuation schemes. However, the future ability and willingness of the government to support a level of age-pension that will provide those dependent on it with a sufficient standard of living is now open to question. This is of particular concern for women as almost 80 per cent of retired women rely on government pensions as their main source of income. Furthermore, many women have only a limited ability to accumulate a sufficient pool of funds through superannuation to finance their retirement. This paper argues that there is a need for a careful appraisal of the alternative retirement income options of Australian women in order to ensure that they will be able to achieve a secure and sufficient standard of living.